Financial Management Behavior among Female Sex Workers: The Roles of Financial Literacy, Financial Attitude, and Hedonic Lifestyle - Buana Hepi; Latifah Putranti (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
Financial management behavior is essential for achieving financial well-being, particularly among economically vulnerable populations. Female sex workers represent an important context for financial behavior research because they often face irregular income, social stigma, limited access to formal financial services, and inadequate financial education, which may increase their financial vulnerability. This study examines the effects of financial literacy, financial attitude, and hedonic lifestyle on financial management behavior among female sex workers in the Pasar Kembang Localization, Yogyakarta. A quantitative approach was employed using a survey method and purposive sampling technique. Data were collected from 141 respondents through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial literacy has a positive and significant effect on financial management behavior, suggesting that greater financial knowledge improves individuals’ ability to manage, save, and plan their finances. Financial attitude also has a positive and significant influence, indicating that favorable beliefs and values regarding money management encourage responsible financial decision-making. In contrast, hedonic lifestyle negatively and significantly affects financial management behavior, implying that pleasure-oriented consumption and impulsive spending weaken financial discipline and long-term financial planning. The model explains 40.8% of the variance in financial management behavior. These findings highlight the importance of enhancing financial literacy and promoting positive financial attitudes while reducing excessive hedonic consumption among financially vulnerable women. The study contributes to the financial behavior literature by providing evidence from a marginalized population and offers practical implications for developing inclusive financial education and empowerment programs.